Physical Origin of the Optical Degradation of InAs Quantum Dot Lasers - Buffolo, Matteo; Samparisi, Fabio; De Santi, Carlo; Jung, Daehwan; Norman, Justin; Bowers, John E.; Herrick, Robert W.; Meneghesso, Gaudenzio; Zanoni, Enrico; Meneghini, Matteo (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2019)
We present an extensive analysis of the physical mechanisms responsible for the degradation of 1.3-mu m InAs quantum dot lasers epitaxially grown on Si, for application in silicon photonics. For the first time, we characterize the degradation of the devices by combined electro-optical measurements, electroluminescence spectra, and current-voltage analysis. We demonstrate the following original results: when submitted to a current step-stress experiment: 1) QD lasers show a measurable increase in threshold current, which is correlated to a decrease in slope efficiency; 2) the degradation process is stronger, when devices are stressed at current higher than 200 mA, i.e., in the stress regime, where both ground-state and excited-state emission are present; and 3) in the same range of stress currents, an increase in the defect-related current components is also detected, along with a slight decrease in the series resistance. Based on the experimental evidence collected within this paper, the degradation of QD lasers is ascribed to a recombination-enhanced defect reaction (REDR) process, activated by the escape of electrons out of the quantum dots.
Keywords: TEMPERATURE-DEPENDENCE; THRESHOLD CURRENT; SI; INJECTION